Chlorinated Electron Acceptor Abundance Drives Selection of Dehalococcoides mccartyi (D. mccartyi) Strains in Dechlorinating Enrichment Cultures and Groundwater Environments - Pérez-de-Mora, Alfredo; Lacourt, Anna; McMaster, Michaye L.; Liang, Xiaoming; Dworatzek, Sandra M.; Edwards, Elizabeth A. (Frontiers in Microbiology, 2018)
Dehalococcoides mccartyi (D. mccartyi) strains differ primarily from one another by the number and identity of the reductive dehalogenase homologous catalytic subunit A (rdhA) genes within their respective genomes. While multiple rdhA genes have been sequenced, the activity of the corresponding proteins has been identified in only a few cases. Examples include the enzymes whose substrates are groundwater contaminants such as trichloroethene (TCE), cis-dichloroethene (cDCE) and vinyl chloride (VC). The associated rdhA genes, namely tceA, bvcA, and vcrA, along with the D. mccartyi 16S rRNA gene are often used as biomarkers of growth in field samples. In this study, we monitored an additional 12 uncharacterized rdhA sequences identified in the metagenome in the mixed D. mccartyi-containing culture KB-1 to monitor population shifts in more detail. Quantitative PCR assays were developed for 15 D. mccartyi rdhA genes and used to measure population diversity in 11 different sub-cultures of KB-1, each enriched on different chlorinated ethenes and ethanes. The proportion of rdhA gene copies relative to D. mccartyi 16S rRNA gene copies revealed the presence of multiple distinct D. mccartyi strains in each culture, many more than the two strains inferred from 16S rRNA analysis. The specific electron acceptor amended to each culture had a major influence on the distribution of D. mccartyi strains and their associated rdhA genes. We also surveyed the abundance of rdhA genes in samples from two bioaugmented field sites (Canada and UK). Growth of the dominant D. mccartyi strain in KB-1 was detected at the UK site. At both field sites, the measurement of relative rdhA abundances revealed D. mccartyi population shifts over time as dechlorination progressed from TCE through cDCE to VC and ethene. These shifts indicate a selective pressure of the most abundant chlorinated electron acceptor, as was also observed in lab cultures. These results also suggest that reductive dechlorination at contaminated sites is brought about by multiple strains of D. mccartyi whether or not the site is bioaugmented. Understanding the driving forces behind D. mccartyi population selection and activity is improving predictability of remediation performance at chlorinated solvent contaminated sites.